Konservasi Catan Dinding Masjid Lama Tok Machap Dan Galeri Cheng Ho, Melaka - Mat Isa, Musrizal (2017)
This study discusses the conservation of wall paintings carried out at Masjid Lama Tok Machap, Alor Gajah and Cheng-Ho Gallery, Stadhuys, Melaka. The study conducted at these two sites is aimed at identifying the types of wall paintings, the techniques used to produce the wall paintings, the type and material used, the conditions and deterioration of the wall paintings, and why the deterioration occurs. The conservation of wall paintings was viewed from two different angles, namely; (i) the condition of the surface of the paint layer, and (ii) the condition of the surface rendering / material support. The causes of deterioration was seen in terms of (i) the effects of water, (ii) the effects of elements such as light, wind and deposits on the surface of the paintings such as insect nests and animal dropping’s, and (iii) past mistakes in restoration work.